The impact of hedonic shopping value, shopping lifestyle, and positive emotions on consumer purchasing decisions at Traveloka - Hazizah Hazizah; I Putu Sudhyana Mecha; Eka Afrida Ermawati (Journal of Applied Sciences in Travel and Hospitality, 2021)
Traveloka is an internet-based tourist information or travel application that allows users to search for and purchase a variety of products and services by online platform, including transportation, lodging, lifestyle, and financial services. Despite the fact that Traveloka is well-known among the general public, there is still lack of knowledge that tourism industry has not used it as promotional and sales media for its products and services. This research was conducted at Banyuwangi in order to determine the impact of partial and simulta-neous hedonic shopping value, shopping lifestyle, and positive emotions on consumer purchasing decisions at Traveloka. The SPSS Version 22 application was used to conduct the research, which included multiple line-ar regression analysis procedures, multiple correlation coefficients, coefficients of determination, T-test, and F-test. Sample size of this study were 100 respondents based on purposive sampling. It showed that hedonic shopping value, shopping lifestyle, and positive emotions all have both partial and simultaneous significant impact on customer purchasing decisions at Traveloka, so conventional tourism industry who de-cides to join the Traveloka are expected to be able to offer and sell tourism products or services that are able to provide and adapt into consumer shopping lifestyles, for example by providing promotion, discounts, and cashback for tour packages or services. Therefore, the results of this research can be applied as recommenda-tion for tourism industry, especially for travel agents who has been joined Traveloka as a member so that they can be more competitive in this digitalization era.